THE ROLE OF PARENTS IN ENCOURAGING SELF-DIRECTED LEARNING IN PRESCHOOL CHILDREN (A COMPARATIVE STUDY BETWEEN TRADITIONAL FAMILIES AND MODERN FAMILIES) - Sandi Pratama; Abdillah S; Nur Faisah Atirah (Lembaga Penelitian Mahasiswa Penalaran UNM, 2024)
This research explains the role of parents in implementing the concept of